Toxicity in Animals: Target Species - N. Woodward, K. (Current Pharmaceutical Biotechnology, 2012)
The macrocyclic lactone endectocides typified by ivermectin are safe and effective drugs when used according to label directions. However, off-label use, misuse and overdosing can result in toxicity in animal patients as revealed by pharmacovigilance activities. Preclinical toxicity studies demonstrates that the major clinical signs of toxicity are those associated with neurotoxic effects and these are the most common adverse drug reactions noted in overdosed treated animals. Subpopulations of some strains or breeds of some species appear to be uniquely sensitive to the neurotoxic effects of the macrocyclic lactones due to enhanced brain penetration by these drugs as a result of a deficiency in P-glycoprotein arising as a result of a mutation in the MDR1 gene.
Keywords: ivermectin